Internasional Pengabdian Kepada Masyarakat di Komunitas ASEAN ‎di Era Digitalisasi dengan Program Sustainable Development Goals ‎‎(SDGs)‎ - Azizah , Nurul (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2022)
Empowerment to the international community in the ASEAN countries aims to answer the challenges of the times in the era of digitalization. This empowerment was written together with the cross-border empowerment team, namely Indonesia, Malaysia, Brunei Darus Salam, Thailand, Madagascar, Uzbekistan, and Japan, as well as members of the cross-country lecturer collaboration association or connecting lecturers across countries. The preliminary study on this international empowerment is to implement Muslim community-based empowerment in the Asia Pacific regions. Methods used through international webinars. The participants were Ma’had Aly students at the Salafiyah Syafi’iyah Sukorejo Situbondo Islamic Boarding School. The conclusion of this devotion is the Islamic Culture Webinar”. This goes smoothly using four foreign languages: English, Arabic, Malay, and French. The expected recommendations for this empowerment activity become a scientific tradition that is beneficial to academics and society at large.